1994
DOI: 10.1115/1.2919480
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Algorithms as an Approach to Configuration and Topology Design

Abstract: The genetic algorithm, a search and optimization technique based on the theory of natural selection, is applied to problems of structural topology design. An overview of the genetic algorithm will first describe the genetics-based representations and operators used in a typical genetic algorithm search. Then, a review of previous research in structural optimization is provided. A discretized design representation, and methods for mapping genetic algorithm “chromosomes” into this representation, is then detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
124
0
3

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(127 citation statements)
references
References 16 publications
0
124
0
3
Order By: Relevance
“…Hence, the original '0-1' optimization problem was attacked directly by using a bit-array representation and a genetic algorithm. The work of Sandgren and his co-workers, using bit-array representation, has been extended by Jakiela and his coworkers [3][4][5], by Schoenauer and his co-workers [6,7,9], by Fanjoy and Crossley [8,10], and, more recently, by Wang and Tai [11]. Although all these extensions can well prevent checkerboard patterns by exploiting a connectiva Corresponding author: matthieu.domaszewski@utbm.fr ity restriction, the other numerical instabilities in structural topology optimization such as mesh dependency and one-node connections still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the original '0-1' optimization problem was attacked directly by using a bit-array representation and a genetic algorithm. The work of Sandgren and his co-workers, using bit-array representation, has been extended by Jakiela and his coworkers [3][4][5], by Schoenauer and his co-workers [6,7,9], by Fanjoy and Crossley [8,10], and, more recently, by Wang and Tai [11]. Although all these extensions can well prevent checkerboard patterns by exploiting a connectiva Corresponding author: matthieu.domaszewski@utbm.fr ity restriction, the other numerical instabilities in structural topology optimization such as mesh dependency and one-node connections still exist.…”
Section: Introductionmentioning
confidence: 99%
“…However, smoothing is based on image processing, which ignores the underlying problem [9]. Moreover, experiments indicated that only higher-order finite element methods with simple GA operators can eliminate the checkerboard-like material distribution in the solution [13]. Furthermore, it is obvious that using higher-order finite element methods will substantially increase computation cost.…”
Section: Introductionmentioning
confidence: 99%
“…In the early studies, a genetic algorithm (GA) was used for structural topology optimization using single point crossover and bitwise mutation operators [4]. Extending the idea of using GA, the structural optimization problems with different kinds of objective functions and constraints were solved.…”
Section: Introductionmentioning
confidence: 99%